Menyandera Timur Tengah - Sihbudi, M. Riza (Subtitle on cover:Kebijakan AS dan Israel atas negara-negara Muslim, 2007)
Ambiguity of the U.S. and Israel policies on socioeconomic and politics for Middle East countries.
Includes bibliographical references (p. [412]-416) and index.
Ambiguity of the U.S. and Israel policies on socioeconomic and politics for Middle East countries.
Keywords: United States / Foreign relations / Israel. / http://id.loc.gov/authorities/subjects/sh2007100074; Israel / Foreign relations / United States. / http://id.loc.gov/authorities/subjects/sh2008104913; Middle East / Foreign relations / United States. / http://id.loc.gov/authorities/subjects/sh89002448; United States / Foreign relations / Middle East. / http://id.loc.gov/authorities/subjects/sh89002449